The Role of The Teaching Campus Program in Improving Teaching Skills and Soft Skills of Accounting Education Students - Yati, Nur Shofy; Jatmika, Surya (Proceedings International Conference on Education Innovation and Social Science, 2025)
This study is to describe the implementation, obstacles, and impact of the Teaching Campus Program in improving the teaching skills of students of the Accounting Education Study Program, University of Muhammadiyah Surakarta. The research with a case study research design was carried out through interview and documentation data collection techniques involving Field Supervisors and programparticipant students. Theresults of the study show that the implementation of the Teaching Campus Program is carried out in one semester through three stages, namely the preparation, assignment, and post-assignment period. Activities began with debriefing, observation, coordination, planning, and the implementation of programs in target schools. The problems encountered are the limitations of monitoring by DPL due to distance and schedule density, dificulties for students to manage time between programs and lectures, limited infrastructure facilities at school, and dificulties in creating interesting learning for students. The positive impact obtained by students includes improving teaching skills, time management, social empathy, creativity, innovation, problem-solving skills, leadership, and other soft skills. In addition, this program also encourages students' professionalism and confidence, while providing real experience in the world of education. Regular evaluations every two weeks play an important role in monitoring program implementation and overcoming obstacles that arise. Therefore, the Teaching Campus Program makes a significant contribution to the development of pedagogic and professional competencies of prospective educator students.